Short stature, brachydactyly, and Peters' anomaly (Peters'-plus syndrome): confirmation of autosomal recessive inheritance. - de Almeida, J C (1991)
Two sibs with a phenotype characterised by short stature, brachydactyly, and ocular anomalies (Peters' anomaly) are reported (Peters'-plus syndrome). The consanguinity is in agreement with the proposed autosomal recessive inheritance.